Analyses of hyperspectral imaging microscopy data sets of semiconducting 2D materials - Dong,X; Yetisen,AK; Tian,H; Dong,J; Koehler,MH; Jakobi,M; Koch,AW (Applied Physics Express, 2020)
The unique optical properties of two-dimensional (2D) materials are largely dependent on the number of atomic layers. Hyperspectral imaging microscopy shows large potential for rapid and accurate thickness mapping. To process the acquired hyperspectral data set and to deal with pixel-level spectra remain a challenge for further application. In this work, two quantitative classification strategies including linear unmixing and spectral peak mapping were conducted to characterize a multilayer semiconducting MoS2 flake with nanoscale thickness variations. The comparative study paves the way to identify 2D semiconducting materials with random layer numbers (monolayer, bilayer, and few-layer) in both laboratory and industry.